Quemadmodum Desiderat Cervus, the Psalm 42 (41): artistic interpretations and imagery. - Rosângela Aparecida da Conceição (Anastasis: Research in Medieval Culture and Art, 2016)
This article presents the analysis of the artistic interpretations and the imaginary representations of Psalm 41 (42), present in the motif of the chained deer that was represented in the ecclesiastical textiles of the Cathedral of Brandenburg, dating from the third quarter of the 14th century, with reproductions executed in the second half of the 19th century and the beginning of the 20th century, with some copies in the Historical and Artistic Collection of the Venerable Third Order of Saint Francis of Penance of the City of São Paulo (VOTSFPCSP) and the Collection of the São Bento Monastery in São Paulo. In addition to textiles, we have the analysis of the Wilton diptych (c.1395-9), belonging to the National Gallery of London, as well as the relief on the altar of the Chapel of the Blessed Sacrament of the Abbey Basilica of Our Lady of the Assumption. Our analysis has as a theoretical basis 'The Commentaries on the Psalms' of Saint Augustine (1997), the work of Albert Rouet (1994) that deals with the relation between art and liturgy, methodology for the study of the image and its uses by Bock (1859 ), EH Gombrich (2012a, 2012b) and Panofsky (1990, 1995), with the support of the study in heraldry by William Berry (1828).